Negative current collector, secondary battery and electronic equipment

By introducing copper-aluminum alloy and pore structure into the negative electrode current collector and combining with the method of embedding the negative electrode active material layer, the problem of degradation of mechanical properties and weak binding force of the copper foil current collector is solved, and the charging and discharging performance and safety performance of the battery are significantly improved.

CN119812351APending Publication Date: 2025-04-11SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411992386.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When the prior art improves the bonding force between the copper foil current collector and the active material, the mechanical properties of the copper foil current collector are greatly reduced, and the bonding force between the copper foil and the negative electrode active material is weak, resulting in reduced battery charge and discharge performance and micro-short circuit problems.

Method used

A negative electrode current collector containing copper-aluminum alloy is used, with pores on the surface, a Brinell hardness of 80HB to 200HB, a tensile strength of 300MPa to 500MPa, an average roughness Ra on the surface of the copper matrix is ​​10nm to 200nm, and a negative electrode active material layer is embedded on the surface of the copper matrix.

Benefits of technology

The bonding force and peeling force between the negative electrode active material and the negative electrode current collector are improved, the stability of the negative electrode active material on the current collector surface is enhanced, and the charging and discharging performance and micro-short circuit problems caused by the peeling of the active material and the current collector after multiple cycles of the battery are avoided, and the cycle life and safety performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224258510000091
    Figure BDA0005224258510000091
  • Figure BDA0005224258510000101
    Figure BDA0005224258510000101
  • Figure BDA0005224258510000102
    Figure BDA0005224258510000102
Patent Text Reader

Abstract

The invention belongs to the technical field of current collector preparation, and particularly relates to a negative electrode current collector, a secondary battery and electronic equipment. The negative current collector comprises a copper substrate, at least one surface of the copper substrate is provided with pores, and the copper substrate comprises a copper-aluminum alloy; and the Brinell hardness of the negative current collector is 80-200HB, and the Brinell hardness is obtained by adopting a national standard GB / T231.1-2018 hard alloy Brinell hardness test method. The surface of the negative electrode current collector is provided with pores, the interior of the negative electrode current collector is of a complete solid structure, the Brinell hardness of the negative electrode current collector is 80-200 HB, more pores exist on the basis of guaranteeing the mechanical property of the negative electrode current collector, more attachment areas are provided for a negative electrode active material, the binding force between the active material and the negative electrode current collector is improved, and the service life of the negative electrode current collector is prolonged. The stability of the negative electrode active material on the surface of the negative electrode current collector is enhanced, the defect that the hardness, the strength, the chemical corrosion resistance and other properties are greatly reduced after the copper foil forms a porous structure in the prior art is overcome, and the cycle performance and the safety performance of the battery are favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of current collector preparation, and specifically relates to a negative electrode current collector, a secondary battery and an electronic device. Background Art

[0002] Secondary batteries are usually composed of a positive electrode, a negative electrode, a separator and an electrolyte. The main material of the negative electrode is usually a carbon material or a silicon material, which is loaded on a copper foil current collector and formed into a stable negative electrode sheet through processes such as rolling and baking. The importance of copper foil in ion batteries is self-evident. However, after multiple cycles, the battery negative electrode sheet often reduces the charge and discharge performance due to the peeling of the negative electrode active material and the negative electrode current collector, and even causes a micro short circuit in severe cases, laying hidden dangers for subsequent thermal runaway and battery failure. Summary of the invention

[0003] The present application provides a negative electrode current collector, a secondary battery and an electronic device. On the one hand, the present application solves the problem that the copper foil current collector is treated in the prior art to improve its bonding strength with the active material, but the mechanical properties of the copper foil current collector are greatly reduced. On the other hand, the present application solves the problem that the bonding strength between the copper foil and the negative electrode active material is weak in the prior art.

[0004] In order to solve the above problems, according to one aspect of the present application, a negative electrode current collector is provided, comprising a copper substrate, the copper substrate having pores on at least one surface, and the copper substrate comprises a copper-aluminum alloy; the Brinell hardness of the negative electrode current collector is 80HB to 200HB, and the Brinell hardness is obtained using the national standard GB / T231.1-2018 cemented carbide Brinell hardness test method.

[0005] Furthermore, the content of the copper-aluminum alloy in the copper matrix is ​​2 g / m 2 ~40g / m 2 .

[0006] Furthermore, the tensile strength of the negative electrode current collector is 300 MPa to 500 MPa.

[0007] Furthermore, the average roughness Ra of the copper substrate surface is 10nm to 200nm.

[0008] Furthermore, the copper matrix further comprises trace elements, and the trace elements include iron, tin, sulfur and zinc; the content of the trace elements in the copper matrix is ​​less than 0.01wt%.

[0009] Furthermore, the copper-aluminum alloy includes CuAl2, and the content of CuAl2 in the copper matrix decreases from the surface of the copper matrix to the inside of the copper matrix.

[0010] Furthermore, the average diameter of the pores is 50 nm to 100 μm.

[0011] In order to solve the above problems, according to one aspect of the present application, a secondary battery is provided, comprising a negative electrode plate, wherein the negative electrode plate comprises the above-mentioned negative electrode collector and a negative electrode active material layer arranged on at least one surface of the negative electrode collector, and the negative electrode active material layer is embedded in the pores on the surface of the negative electrode collector.

[0012] Furthermore, the average peeling force between the negative electrode active material layer and the negative electrode current collector is ≥10 N / m.

[0013] According to one aspect of the present application, an electronic device is provided, comprising the above-mentioned secondary battery, wherein the secondary battery serves as a power supply for the electronic device.

[0014] The technical solution of this application has the following advantages:

[0015] The surface of the negative electrode current collector of the present application has pores, and the interior is a complete solid structure, and contains copper-aluminum alloy, so that the Brinell hardness of the negative electrode current collector is 80HB to 200HB, so that there are more pores on the basis of ensuring the mechanical properties of the negative electrode current collector, providing more attachment area for the negative electrode active material, improving the binding force between the active material and the negative electrode current collector, and strengthening the stability of the negative electrode active material on the surface of the negative electrode current collector, overcoming the defects of the prior art that the copper foil forms a porous structure and the hardness, strength and chemical corrosion resistance are greatly reduced. Further, with the improvement of the binding force between the active material and the negative electrode current collector, the loading amount of the active material on the surface of the negative electrode current collector can be increased, the coating surface density can be increased, and the problems such as the reduction of charge and discharge performance or micro short circuit caused by the peeling of the active material and the current collector after multiple cycles of the battery can be reduced, thereby improving the electrical performance and safety performance of the battery. DETAILED DESCRIPTION

[0016] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.

[0017] In one embodiment of the present application, a negative electrode current collector is provided, comprising a copper substrate, the copper substrate having pores on at least one surface, and the copper substrate comprises a copper-aluminum alloy; the Brinell hardness of the negative electrode current collector is 80HB to 200HB, and the Brinell hardness is obtained using the national standard GB / T 231.1-2018 cemented carbide Brinell hardness test method.

[0018] The surface of the negative electrode current collector of the present application has pores, and the interior is a complete solid structure. The Brinell hardness of the negative electrode current collector is 80HB to 200HB. On the basis of ensuring the mechanical properties of the negative electrode current collector, there are more pores, which provide more attachment area for the negative electrode active material, improve the binding force between the negative electrode active material and the negative electrode current collector, and strengthen the stability of the negative electrode active material on the surface of the negative electrode current collector. At the same time, the hardness, strength and chemical corrosion resistance of the negative electrode current collector can also be improved. Furthermore, with the improvement of the binding force between the negative electrode active material and the negative electrode current collector, the loading amount of the active material on the surface of the negative electrode current collector can be increased, so that the coating surface density is improved, and the negative electrode active material and the negative electrode current collector are peeled off after multiple cycles of the battery, resulting in reduced charge and discharge performance or micro-short circuits. Problems such as the cycle life and safety performance of the battery are improved.

[0019] Illustratively, the Brinell hardness of the negative electrode current collector is one of 80HB, 100HB, 120HB, 140HB, 160HB, 180HB, 200HB, 90HB to 150HB, 115HB to 175HB, or 132HB to 182HB.

[0020] In some embodiments, the content of the copper-aluminum alloy in the copper matrix is ​​2 g / m 2 ~40g / m 2 The present invention introduces aluminum into the negative electrode current collector to form a copper-aluminum intermetallic compound or solid solution as a strengthening phase, which significantly improves the tensile strength and hardness of the negative electrode current collector. For example, the content of copper-aluminum alloy in the copper matrix is ​​2g / m 2 , 5g / m 2 , 8g / m 2 , 13g / m 2 , 20g / m 2 , 25g / m 2 , 30g / m 2 , 35g / m 2 , 38g / m 2 , 40g / m 2 , 3g / m 2 ~28g / m 2 , 17g / m 2 ~23g / m 2 , 10g / m 2 ~33g / m 2 One of them.

[0021] In some embodiments, the tensile strength of the negative electrode current collector is 300MPa to 500MPa. This indicates that the negative electrode current collector of the present application has high tensile strength, good fracture resistance and mechanical properties. When the tensile strength is lower than 300MPa, the battery is not easy to pass the extrusion test and is prone to failure. Exemplarily, the tensile strength of the negative electrode current collector is one of 300MPa, 350MPa, 400MPa, 450MPa, 500MPa, 330MPa to 480MPa, and 380MPa to 420MPa.

[0022] In some embodiments, the average roughness Ra of the copper substrate surface is 10nm to 200nm. The copper substrate surface of the present application has more pores, so that the surface roughness of the copper substrate is increased, which can provide more attachment area for the negative electrode active material, so that the average specific surface area can reach 10 to 18m 2 / g, significantly improving the peeling force between the negative electrode active material and the negative electrode current collector. Under the same compaction density, the average peeling force between the negative electrode current collector and the negative electrode active material of the present application is significantly improved, which can increase the loading amount of the negative electrode active material on the negative electrode current collector and enhance the stability of the surface of the negative electrode active material and the negative electrode current collector. Exemplarily, the average roughness Ra of the copper substrate surface is one of 10nm, 30nm, 50nm, 80nm, 100nm, 130nm, 150nm, 180nm, 200nm, 20nm to 90nm, and 110nm to 190nm.

[0023] In some embodiments, the copper matrix further comprises trace elements, including iron, tin, sulfur and zinc; the content of the trace elements in the copper matrix is ​​less than 0.01 wt %. The presence of trace elements is beneficial to improving the strength and corrosion resistance of the negative electrode current collector.

[0024] In some embodiments, the copper-aluminum alloy includes CuAl2, and the content of CuAl2 in the copper matrix decreases from the surface of the copper matrix to the inside of the copper matrix. CuAl2 has a solid solution strengthening effect, which helps to improve the tensile strength and hardness of the negative electrode current collector. Furthermore, the content of CuAl2 in the copper matrix decreases from the surface of the copper matrix to the inside of the copper matrix, so that the copper matrix can have a complete solid structure, the pores only exist on the surface of the copper foil, and the copper matrix still has a complete supporting function, ensuring the mechanical properties of the negative electrode current collector, avoiding the defect of the prior art that through holes are easily formed when the sublimation points of different phases are used for dealloying, affecting the mechanical properties of the negative electrode current collector. In some embodiments, the copper-aluminum alloy accounts for 25wt% to 40wt% of the negative electrode current collector. This can ensure that the negative electrode current collector has a high tensile strength.

[0025] In some embodiments, the average diameter of the pores is 50nm to 100μm, and the average depth is 100nm to 5μm. The present application regulates the average diameter and average depth of the pores on the surface of the copper substrate, which helps to control the surface roughness of the copper substrate, improve the binding force and stripping force between the active material and the surface of the negative electrode current collector, and increase the loading amount of the negative electrode active material. Exemplarily, the average diameter of the pores is one of 50nm, 100nm, 500nm, 1μm, 5μm, 10μm, 20μm, 40μm, 80μm, 100μm, 200nm to 800nm, 900nm to 50μm, and 30μm to 90μm.

[0026] In one embodiment of the present application, a method for preparing a negative electrode current collector is provided, comprising the following steps:

[0027] (1) Preheating copper foil;

[0028] (2) spraying molten aluminum onto at least one surface of the copper foil by a spraying method;

[0029] (3) Dealloying treatment.

[0030] In some embodiments, in step (1), the thickness of the copper foil is 3.5 μm to 15 μm; the temperature after preheating is 200° C. to 500° C., at which the splashing of molten aluminum droplets formed during the spraying process of step (2) can be reduced.

[0031] In some embodiments, in step (2), the aluminum material is heated to 660-750°C to obtain a molten aluminum metal liquid with good fluidity to form molten aluminum. During the spraying process, the average diameter of the aluminum droplets formed by the molten aluminum is controlled to be 50nm-2μm, and can be evenly distributed on the surface of the copper foil.

[0032] In some embodiments, in step (2), after spraying, the aluminum droplets are solidified and then rolled to embed or adhere the aluminum particles to the surface of the copper foil. It should be noted that before rolling, the temperature of the aluminum foil surface is 80°C to 300°C.

[0033] In some embodiments, a heat treatment step is further included after rolling, and the heat treatment temperature is 160°C to 500°C and the time is 30min to 120min. The copper foil after rolling is heated to 160°C to 500°C for heat treatment to reach the phase change point, and the solid phase diffuses on the surface of the copper foil to form a uniform copper-aluminum alloy. After 30min to 120min, a better solid phase diffusion distribution is achieved. The average thickness of the copper-aluminum alloy layer formed in this process should be 100nm to 5μm.

[0034] In some embodiments, the step (3) further includes spray cleaning before the dealloying treatment; the cleaning liquid may be but is not limited to anhydrous ethanol, water, etc.

[0035] In some embodiments, the step (3), the dealloying treatment includes chemically corroding the copper foil with an alkali solution and an acid solution in sequence to complete the dealloying treatment, and after the dealloying, the copper-aluminum alloy includes copper and a portion of the aluminum-copper alloy phase CuAl2, and most of the aluminum-copper alloy phase Al4Cu9 is removed; after secondary cleaning, a copper foil having a nano-scale and / or micro-scale porous layer on the surface is obtained. It should be noted that copper foil is a common material in the art, and this application does not impose specific restrictions on this. The cleaning solution for the secondary cleaning can be, but is not limited to, a well-known solvent such as anhydrous ethanol.

[0036] In some embodiments, the alkali solution is preferably a sodium hydroxide aqueous solution or a potassium hydroxide aqueous solution, and the concentration of the alkali solution is 5 to 20 wt %.

[0037] In some embodiments, the acid solution is preferably at least one of a hydrochloric acid aqueous solution, a sulfuric acid aqueous solution, and a phosphoric acid aqueous solution, and the concentration of the acid solution is 5 to 20 wt %.

[0038] In some embodiments, during the dealloying treatment, the temperature is 25° C. to 50° C. and the time is 5 min to 30 min.

[0039] The present application adopts a spraying method to evenly distribute molten aluminum on the surface of the copper foil, and solid-phase diffusion is formed into copper, aluminum, and copper-aluminum alloy phases after heat treatment. After dealloying treatment, part of the copper-aluminum alloy phase and elemental aluminum are removed, so that the copper foil surface forms a composite structure with uniform pore distribution and solid copper foil support, which will not form penetration and ensure the stability of the copper foil. Compared with the copper foil with dealloying treatment in the prior art, the negative electrode current collector of the present application contains copper-aluminum alloy, and the problem of a significant decrease in the mechanical properties of the copper foil will not occur, and the bonding force between the copper foil and the active material can also be improved.

[0040] In one embodiment of the present application, a secondary battery is provided, including a negative electrode plate, the negative electrode plate including the above-mentioned negative electrode current collector, and the negative electrode active material layer is embedded in the pores on the surface of the current collector. In the present application, the negative electrode active material is embedded in the pores of the negative electrode current collector, which can improve the binding force between the negative electrode active material and the copper foil current collector, improve the peeling force, and avoid the reduction of charge and discharge performance due to the peeling of the active material layer and the current collector during the cycle, causing micro short circuits and the like.

[0041] In some embodiments, the average peeling force between the negative electrode active material layer and the negative electrode current collector is ≥10N / m, and the average peeling force is obtained according to the peeling test method. The present application regulates the peeling force between the negative electrode active material layer and the negative electrode current collector, so that the negative electrode active material is not easy to fall off during the charge and discharge process, thereby improving the cycle performance and safety performance of the battery. In some embodiments, the average peeling force between the negative electrode active material layer and the negative electrode current collector is 10 to 15N / m, for example, it can be a range value of one or any two of 10N / m, 11N / m, 13N / m, and 15N / m.

[0042] The secondary battery described in the present application includes a sodium ion secondary battery, a lithium ion secondary battery, etc., preferably a sodium ion secondary battery. The negative electrode sheet includes the above-mentioned negative electrode current collector and an active material layer arranged on at least one surface of the negative electrode current collector, and the active material of the active material layer includes at least one of hard carbon, silicon carbon, and graphite.

[0043] In one embodiment of the present application, an electronic device is provided, comprising the above-mentioned secondary battery, wherein the secondary battery serves as a power supply for the electronic device.

[0044] Example 1

[0045] This embodiment provides a method for preparing a negative electrode current collector, comprising the following steps:

[0046] Preheating copper foil: A copper foil with a thickness of 7 μm is unwound by an unwinding mechanism and preheated to 300°C by a hot roller device.

[0047] Melt spraying: The aluminum material is heated to 700℃ to form a molten liquid, and then sprayed on the two surfaces of the moving copper foil through a thermal spray device. The average diameter of the aluminum droplets is 1μm (the diameter of the aluminum droplets can be obtained through an optical microscope test). After the average surface temperature of the copper foil drops to 200℃, the copper foil enters the heat treatment zone through a roller pressing device, the temperature is controlled at 300℃, and it continues to run in the zone for 30 minutes. After being sprayed and cleaned with anhydrous ethanol and deionized water, a copper-aluminum alloy layer is obtained.

[0048] Dealloying treatment: After cleaning, the foil is immersed in a 7.5wt% NaOH solution for 5 minutes, and then immersed in a 5wt% HCl solution for 5 minutes, and then washed with anhydrous ethanol to obtain pores on both surfaces of the copper foil, that is, a negative electrode current collector is obtained.

[0049] The test method of the parameters of the negative electrode current collector: the Brinell hardness of the negative electrode current collector is tested by the national standard GB / T 231.1-2018 hard alloy Brinell hardness test method; the content of copper-aluminum alloy in the negative electrode current collector is tested by XRD diffractometer; the tensile strength of the negative electrode current collector is tested by static tensile method; the average roughness Ra of the surface of the negative electrode current collector is tested by surface roughness measuring instrument, and the roughness of 3 different positions on the surface of the negative electrode current collector is tested and the average value is taken; the content of trace elements in the negative electrode current collector is tested by EDS energy spectrometer. The average diameter of the pores on the surface of the negative electrode current collector is tested by scanning electron microscopy, and the average pore diameter of all pores within the range of 5μm×5μm in the spectrum is taken; the average thickness of the negative electrode current collector is 7.5μm, and the thickness of the negative electrode current collector is tested by vernier caliper at 3 different positions of the negative electrode current collector and the average value is taken.

[0050] Extrusion safety performance test of battery cells: The extrusion safety performance of the batteries of the embodiment and comparative example is tested using the test method 8.1.7 in GB38031-2020 Safety requirements for power batteries for electric vehicles. The test is considered to have passed if no thermal runaway occurs during the entire test process.

[0051] Cycle performance: Use 0.33C constant current to discharge the battery to the lower limit voltage of 1.5V, wait for 10 minutes, and charge it to the upper limit voltage of 4V at 1C constant current, and wait for 10 minutes. Repeat the above steps until the capacity retention rate is less than 80%, then stop the operation and record the total number of cycles. Each charge and discharge is recorded as 1cls.

[0052] This embodiment also provides a method for preparing a negative electrode plate: negative electrode active material (hard carbon), conductive agent carbon nanotubes, and binder sodium carboxymethyl cellulose are mixed in a mass ratio of 88:7:5, solvent water is added to obtain a slurry, the slurry is coated on the above-mentioned copper foil current collector, and the negative electrode plate is obtained after drying.

[0053] This embodiment also provides a method for preparing a positive electrode sheet, comprising: mixing a positive electrode active material (NaNi 0.4 Fe 0.4 Mn 0.2 O2), conductive agent carbon nanotubes, and binder PVDF are mixed to obtain slurry, the slurry is coated on the above aluminum foil, and the positive electrode sheet is obtained after drying.

[0054] This embodiment also provides a method for preparing a battery, comprising:

[0055] The positive electrode sheet, separator, and negative electrode sheet are stacked or wound in sequence, and an electrolyte is injected (the solute in the electrolyte is 0.8M sodium salt NaPF6, and the solvent is composed of ethylene carbonate and dimethyl carbonate in a molar ratio of 1.2:1) to assemble a battery.

[0056] Example 2-18

[0057] Example 2-18 provides a battery, which is basically the same as Example 1, except that the negative electrode current collector is different. The parameters and preparation process of the negative electrode current collector of Examples 2-18 are shown in Table 1-2 respectively.

[0058] Comparative Example 1

[0059] This comparative example provides a battery, which is basically the same as Example 1, except that the negative electrode current collector is different. The negative electrode current collector of this comparative example is a copper foil that has not been subjected to melt spraying dealloying treatment.

[0060] Table 1 Negative electrode current collector parameters provided in various embodiments and comparative examples

[0061]

[0062]

[0063] Table 2 Process parameter adjustment of each embodiment and comparative example

[0064]

[0065] It can be seen from the above results that the Brinell hardness of the negative electrode current collector is regulated to 80HB to 200HB in the present application, and the surface of the negative electrode current collector has pores, which can improve the bonding force between the active material and the negative electrode current collector, and the negative electrode current collector has high mechanical properties such as tensile strength, which is beneficial to improving the cycle performance and safety performance of the battery.

[0066] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection created by this application.

Claims

1. A negative electrode current collector, characterized in that: It includes a copper substrate, at least one surface of the copper substrate has pores, and the copper substrate contains a copper-aluminum alloy; the Brinell hardness of the negative electrode collector is 80HB to 200HB, and the Brinell hardness is obtained by using the national standard GB / T 231.1-2018 hard alloy Brinell hardness test method.

2. The negative electrode current collector according to claim 1, characterized in that: The content of the copper-aluminum alloy in the copper matrix is ​​2 g / m 2 ~40g / m 2 .

3. The negative electrode current collector according to claim 1 or 2, characterized in that: The tensile strength of the negative electrode current collector is 300 MPa to 500 MPa.

4. The negative electrode current collector according to claim 1, characterized in that: The average roughness Ra of the copper substrate surface is 10nm-200nm.

5. The negative electrode current collector according to claim 1, characterized in that: The copper matrix further comprises trace elements, which include iron, tin, sulfur and zinc; the content of the trace elements in the copper matrix is ​​less than 0.01 wt %.

6. The negative electrode current collector according to claim 1, characterized in that: The copper-aluminum alloy includes CuAl2, and the content of CuAl2 in the copper matrix decreases from the surface of the copper matrix to the inside of the copper matrix.

7. The negative electrode current collector according to claim 1, characterized in that: The average diameter of the pores is 50 nm to 100 μm.

8. A secondary battery, characterized in that: The invention comprises a negative electrode sheet, wherein the negative electrode sheet comprises the negative electrode current collector according to any one of claims 1 to 7 and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer is embedded in the pores on the surface of the negative electrode current collector.

9. The secondary battery according to claim 8, characterized in that: The average peeling force between the negative electrode active material layer and the negative electrode current collector is ≥10 N / m.

10. An electronic device, characterized in that: The secondary battery according to claim 8 or 9 is used as a power supply for the electronic device.

Citation Information

Patent Citations

  • Flexible device and preparation method thereof

    CN104993150A

  • Nanoporous copper-silicon negative electrode sheet and preparation method thereof

    CN109148891A

  • Negative electrode multi-stage copper skeleton current collector for lithium metal battery, preparation method thereof and battery containing current collector

    CN111106355A

  • Negative plate and lithium ion battery comprising same

    CN111916753A

  • All-solid-state thick-film lithium battery and preparation method thereof

    CN113871696A